1999
DOI: 10.1002/(sici)1096-8628(19990820)88:4<369::aid-ajmg14>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Linkage analysis of a large swedish kindred provides further support for a susceptibility locus for schizophrenia on chromosome 6p23

Abstract: Several reports have indicated genetic linkage between markers on the short arm of chromosome 6 and schizophrenia. However, significant threshold levels were not always achieved, and the chromosomal regions identified are large and different in different families. One way to decrease the problem of heterogeneity is to study a single extended pedigree. Here we report the analysis of a very large, previously undescribed pedigree from northern Sweden that includes 31 affected individuals. We typed 16 markers span… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(19 citation statements)
references
References 31 publications
0
18
0
1
Order By: Relevance
“…A series of immunohistochemical experiments similarly found reductions in GABA B immunolabeling in hippocampus, prefrontal cortex, inferior temporal cortex, and the entorhinal cortex of subjects with schizophrenia (Ishikawa et al, 2005; Mizukami et al, 2000, 2002). The loci of both the GABBR1 gene (6p21.3) and GABBR2 gene (5q34) have been established as susceptibility loci for schizophrenia (Lindholm et al, 1999; Petryshen et al, 2005). However, one study has found a weak linkage between the GABBR1 gene and schizophrenia (Zai et al, 2005), while two other studies have found no connection (Imai et al, 2002; Zhao et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…A series of immunohistochemical experiments similarly found reductions in GABA B immunolabeling in hippocampus, prefrontal cortex, inferior temporal cortex, and the entorhinal cortex of subjects with schizophrenia (Ishikawa et al, 2005; Mizukami et al, 2000, 2002). The loci of both the GABBR1 gene (6p21.3) and GABBR2 gene (5q34) have been established as susceptibility loci for schizophrenia (Lindholm et al, 1999; Petryshen et al, 2005). However, one study has found a weak linkage between the GABBR1 gene and schizophrenia (Zai et al, 2005), while two other studies have found no connection (Imai et al, 2002; Zhao et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Since Straub et al (1995) and Kendler et al (1996) initially reported the linkage of markers mapped to chromosome 6p24-21 to schizophrenia spectrum disorders, there have been at least 15 additional linkage studies; of these, at least 7 provided supportive evidence for susceptibility loci on chromosome 6p (Schwab et al 1995; Levinson et al 1996; Maziade et al 1997; Lindholm et al 1999; Turecki et al 1997; Straub et al 2002a; Lewis et al 2003). These susceptibility loci span a broad region of 25Mb between D6S296 and D6S291, including four possibly distinct subregions: 6p25-24, 6p24, 6p23-22, and 6p21 (reviewed by Straub et al 2002b).…”
Section: Introductionmentioning
confidence: 99%
“…Associations have also been found for other genetic loci linked to the short arm of chromosome 6. These include the rs111602326 and rs113663679 loci within the ARVD8 gene (MIM 607450) [49], the HLA-DRB1 gene (MIM 142857) [50], and the rs113785696 and rs111341380 loci associated with schizophrenia type 3 (MIM 600511) [51, 52]. …”
Section: Discussionmentioning
confidence: 99%